First direct observation of the built-in electric field and oxygen vacancy migration in ferroelectric Hf0.5Zr0.5O2 film during electrical cycling - Liang Chen; Liang, Zhongxin; Shao, Shixuan; Huang, Qianqian; Tang, Kechao; Ru HUANG (Nanoscale, 2023)
The wake-up and fatigue effects exhibited by ferroelectric hafnium oxide (HfO2) during electrical cycling are two of the most significant obstacles limiting its development and application. Despite a mainstream theory relating these phenomena to the migration of oxygen vacancies and the evolution of the built-in field, no supportive experimental observations from a nanoscale perspective have been reported so far. By combining differential phase contrast scanning transmission electron microscopy (DPC-STEM) and energy dispersive spectroscopy (EDS) analysis, we directly observe the migration of oxygen vacancies and the evolution of the built-in field in ferroelectric HfO2 for the first time. These solid results indicate that the wake-up effect is caused by the homogenization of oxygen vacancy distribution and weakening of the vertical built-in field whereas the fatigue effect is related to charge injection and transverse local electric field enhancement. In addition, using a low-amplitude electrical cycling scheme, we exclude field-induced phase transition from the root cause of the wake-up and fatigue in Hf0.5Zr0.5O2. With direct experimental evidence, this work clarifies the core mechanism of the wake-up and fatigue effects, which is important for the optimization of ferroelectric memory devices.